The relationship between sport tourists' perceived value and destination loyalty: an experience-use history segmentation approach. Issue 2 (3rd April 2018) - Sato, Shintaro; Gipson, Christina; Todd, Samuel; Harada, Munehiko
ABSTRACT: Understanding active sport tourists' profiles and nurturing their destination loyalty are important considerations in the tourism market. Loyal tourists are valuable because they tend to revisit a focal destination and elicit positive word-of-mouth. Focusing on a snow-based active sport tourism context, this study was conducted to examine (1) the usefulness of experience-use history (EUH) as a segmentation tool and (2) the relationship between perceived value factors (i.e. quality, emotional response, monetary price, behavioral price, and destination reputation ) and destination loyalty in each EUH group. Data were collected from the Niseko ski resort in Japan ( N = 328). Based on the EUH variables (i.e. length and frequency of snow-based sport participation), participants were categorized into four segments (i.e. novice, short-active, long-inactive, and expert ). The results showed significant differences among EUH groups in terms of their socio-demographics (e.g. gender, age, and income). A series of regression analyses also showed that each segment's destination loyalty was uniquely enhanced by perceived value factors. Specifically, perceived quality was a significant antecedent of destination loyalty for sport tourists in the novice group. For those in the short-active, long-inactive, and expert groups, perceived emotional response significantly predicted destination loyalty. Perceived reputation of the destination was also important to enhance destination loyalty for the short-active group whereas perceived monetary price was positively associated with the long-inactive group's destination loyalty. Marketing managers in snow-based sport tourism destinations can utilize the findings to increase the loyalty of active sport tourists, which will improve their competitiveness in the marketplace.